Superoxide Dismutase 1 In Vivo Ameliorates Maternal Diabetes Mellitus–Induced Apoptosis and Heart Defects Through Restoration of Impaired Wnt Signaling. (October 2015) - Wang, Fang; Fisher, Steven A.; Zhong, Jianxiang; Wu, Yanqing; Yang, Peixin
Abstract : Background—: Oxidative stress is manifested in embryos exposed to maternal diabetes mellitus, yet specific mechanisms for diabetes mellitus–induced heart defects are not defined. Gene deletion of intermediates of Wingless-related integration (Wnt) signaling causes heart defects similar to those observed in embryos from diabetic pregnancies. We tested the hypothesis that diabetes mellitus–induced oxidative stress impairs Wnt signaling, thereby causing heart defects, and that these defects can be rescued by transgenic overexpression of the reactive oxygen species scavenger superoxide dismutase 1 (SOD1). Methods and Results—: Wild-type (WT) and SOD1-overexpressing embryos from nondiabetic WT control dams and nondiabetic/diabetic WT female mice mated with SOD1 transgenic male mice were analyzed. No heart defects were observed in WT and SOD1 embryos under nondiabetic conditions. WT embryos of diabetic dams had a 26% incidence of cardiac outlet defects that were suppressed by SOD1 overexpression. Insulin treatment reduced blood glucose levels and heart defects. Diabetes mellitus increased superoxide production, canonical Wnt antagonist expression, caspase activation, and apoptosis and suppressed cell proliferation. Diabetes mellitus suppressed Wnt signaling intermediates and Wnt target gene expression in the embryonic heart, each of which were reversed by SOD1 overexpression. Hydrogen peroxide and peroxynitrite mimicked the inhibitory effect of high glucose on Wnt signaling, which was abolished by the SOD1 mimetic, tempol. Conclusions—: The oxidative stress of diabetes mellitus impairs Wnt signaling and causes cardiac outlet defects that are rescued by SOD1 overexpression. This suggests that targeting of components of the Wnt5a signaling pathway may be a viable strategy for suppression of congenital heart defects in fetuses of diabetic pregnancies. Abstract : Supplemental Digital Content is available in the text.